Analysis of Transient Modes of Peltier Thermoelectric Elements under Various Input Influences - Gleb Vasilyev; Oleg Kuzichkin; Dmitry Surzhik; Aleksandr Koskin (Majlesi Journal of Electrical Engineering)
Stationary operation of a thermoelectric system is often not economical due to the impossibility of soft adjustment of the microclimate. The aspect makes relevant the research of the transient modes of Peltier elements and thermoelectric systems built on their basis. The study of the dynamic properties of thermoelectric devices and systems with high accuracy requires the use of complex high-order models, which makes it difficult to obtain analytical solutions. Using the spectral approach and piecewise linear approximation, analytical formulae of the transient modes of Peltier thermoelectric elements for various deviations of control currents are obtained. The calculated relations of piecewise linear approximating functions, spectral densities and time forms of input and output parameters of the model under study are presented. Time diagrams of the temperature response of a particular Peltier element in linear and nonlinear modes are constructed, calculated for the sinusoidal deviation of the control current from the stationary value.